The effects of the home-based exercise during COVID-19 school closure on the physical fitness of preschool children in China - Zhenwen Liang; Cheng Deng; Dan Li; Wai Leung Ambrose Lo; Qiuhua Yu; Zhuoming Chen (Frontiers Media S.A., 2022)
BackgroundSocial distancing and school closures during the COVID-19 pandemic reduced the physical activities of the preschool children living in China. However, the effects of home-based exercise on the physical fitness of Chinese preschool children during COVID-19 school closures are still unknown. This study aimed to investigate the effects of home-based exercise on the physical fitness of Chinese preschool children during COVID-19 school closure.MethodsIn this retrospective analysis, data from 1,608 Chinese preschool children (aged 3-5.5 years) in a second-tier city of Guangdong Province of China (Zhongshan city) were extracted from three successive National Physical Fitness Measurement (NPFM) from 2019 to 2021. NPFM consists of weight, height, and six subtests of physical fitness including 10-m shuttle run test (SRT), standing long jump (SLJ), balance beam walking (BBW), sit-and-reach (SR), tennis throwing (TT), and double-leg timed hop (DTH) tests. The change differences or change ratios of all the items in NPFM between any two successive years from 2019 to 2021 were compared. The exercise profiles about home-based and outdoor exercise before, during, and after COVID-19 school closure were obtained from 185 preschool children via retrospective telephone survey.ResultsBetween 2019 and 2021, 1,608 preschool children were included in this study. We observed larger changes in SLJ, SR, TT, and DTH tests during school closure than after school closure. But the children showed lower reduction rates in the completion time of SRT and BBW. During school closure, higher change ratios in SLJ and TT were observed in the children primarily participating in home-based exercise than those primarily participating in outdoor exercise. However, no statistical differences were observed in the changes in SRT and BBW between home-based and outdoor training groups.ConclusionThe home-based exercise program might be an alternative approach to improve the physical fitness of preschool children during COVID-19 school closure, but could not be beneficial to speed-agility and balance functions. A specific guideline geared toward a home-based exercise program during the COVID-19 outbreak is highly needed.